It Was Me: The Use of Sense of Agency Cues Differs Between Cultures - Bart, Victoria K. E.; Sharavdorj, Erdenechimeg; Bazarvaani, Khishignyam; Munkhbat, Tegshbuyan; Wenke, Dorit; Rieger, Martina (Frontiers in Psychology, 2019)
Sense of agency is the sense of having control over one's own actions and through them events in the outside world. Sense of agency may be estimated by integrating different agency cues. In the present study, we examined whether the use of different agency cues – action-effect congruency, temporal relation between action and effect, and affective valence of effects - differs between Eastern (Mongolian) and Western (Austrian) cultures. In a learning phase, participants learned to associate different actions (keypresses) with positive and negative action effects (smileys). In a test phase, participants performed the same keypresses. After different intervals positive and negative action effects, which were either congruent or incongruent with the previously acquired action-effect associations, were presented. In each trial participants were asked to rate how likely the action effect was caused by themselves or by the computer (authorship ratings). In both groups authorship ratings were higher for congruent compared to incongruent action effects and for positive compared to negative action effects. This indicates that action-effect congruency and affective valence of action effects modulate sense of agency. Further, in both groups the difference between positive and negative effects was higher with congruent effects than incongruent effects. This overadditive effect of action-effect congruency and affective valence might indicate that an integration of different agency cues takes place. Decreasing authorship ratings with increasing interval were observed in Austrians but not in Mongolians. For Mongolians, the temporal chronology of events might be less important when inferring causality. Therefore, information regarding the temporal occurrence of the effect might not be used as an agency cue in Mongolians. In conclusion, some agency cues might be similarly used in different cultures, but the use of others might be culture-dependent.